Extracurricular Management in Schools - Rosidah, Fitria Nur; Sumarsono, Raden Bambang (Universitas Negeri Malang, 2024)
Extracurricular activities are activities that indirectly support intracurricular activities. Extracurricular activities have long-term benefits in the self-development of students. In order for the implementation of extracurricular activities in schools to run effectively and efficiently, schools can implement extracurricular management. The method used in this article uses literature studies from various sources such as google scholar and books. Extracurricular management in schools is carried out through four processes, namely planning, organizing, implementing and evaluating. The four processes are interconnected where the stages are carried out sequentially starting from planning to evaluation. This management process is carried out to achieve extracurricular goals and avoid deviations during extracurricular activities and can take corrective steps before the problem becomes big.